The role of serum lipid profile in the pathogenesis of arterial hypertension - Rafaqat, Saira; Rafaqat, Sana; Klisić, Aleksandra (Archives of Pharmacy, 2024)
Hypertension is a key contributor to the high global burden of cardiovascular morbidity and mortality, due to its increasing prevalence worldwide. In clinical practice, dyslipidemia and hypertension often coexist, possibly because they share similar underlying causes, such as endothelial dysfunction and obesity. Consequently, this review article presents the collective findings on the role of lipid profile parameters in arterial hypertension. Individuals with hypertension often have significantly higher mean serum levels of triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C), while exhibiting lower mean serum levels of high-density lipoprotein cholesterol (HDL-C) compared to those without hypertension. TC and HDL-C play an important role in the pathogenesis of arterial hypertension. However, there is a lack of studies explaining the link between TG and LDL-C and arterial hypertension. Future studies are necessary to fully elucidate the exact mechanisms by which the mentioned lipid parameters contribute to arterial hypertension.
Keywords: arterial hypertension; lipid profile; atherosclerosis